Persepsi Mahasiswa Dalam Pemanfaatan Artificial Intellegence (AI) ChatGPT Sebagai Sumber Informasi - Sari, Tiara Puspita; Yoka, Yoka; Fitri, Yunika; Utami, Intan; Irawan, Bambang (Yayasan Sembilan Pemuda Indonesia, 2026)
This study was conducted on students of the Islamic Religious Education Study Program at Fatmawati Sukarno State Islamic University of Bengkulu from the 2022, 2023, and 2024 cohorts. The purpose of this study is to determine the perceptions of students and teaching staff regarding the use of AI ChatGPT as a source of information. This research is qualitative in nature with a descriptive approach. The data collection techniques include interviews, participant observation, and documentation. Meanwhile, data analysis techniques are carried out through data reduction, data display, data verification, and drawing conclusions in accordance with this research. The results of this study consist of two main findings. First, students’ perceptions of the use of AI ChatGPT as a source of information show various opinions and experiences. Students assess that ChatGPT provides a considerable positive impact, especially in facilitating access to information, answering questions, understanding learning materials, and helping to complete academic tasks. However, there are also negative aspects, namely causing dependency, reducing motivation to read books, and weakening critical thinking skills. Second, the perceptions of teaching staff indicate that lecturers consider ChatGPT as a technological innovation that provides many benefits for both lecturers and students, especially in accelerating information searches, helping to simplify concepts, and supporting the preparation of teaching materials. AI ChatGPT is considered to have a positive impact of around 80–85% as long as it is used wisely. However, ChatGPT can have negative effects if students do not develop and validate the information provided by ChatGPT, which can lead to dependency, reduced critical thinking, and decreased originality.